Hardfacing alloys for excavator teeth coating - Poser B. Maja; Zdraveski, Filip; Petrevski, Martin; Pavlovic, Milos; Jeremic, Vladan (Serbian Welding Society, 2024)
The capacity of the rotоr excavator depends to a significant extent on the backet teeth. Abrasive wear of cutting teeth and cutting edges is typical when digging sand, sandy clay and gravel in common rock environments. Of particular importance is the contribution of the correct geometry of the teeth, their position on the backet, and especially their sharpness, which they lose over time. Over time, teeth become blunt due to abrasive wear and their geometry changes. The digging resistance becomes greater, and therefore the efficiency of the rotor excavator decreases. White cast iron stands out as a base alloy that has wear resistance, but has very low toughness and often brittle fracture under impact loads. Manganese steel, although it has the property of deformation strengthening, has no wear resistance when digging in sand. This condition can be improved by choosing a material more resistant to abrasive action. Excavator teeth that fail due to abrasive wear can be protected from abrasive wear by the use of hardface coating. These hardfacing alloys are presented in this paper.
Keywords: abrasive wear; roto excavator; bucket teeth; hardfacing alloys